The Mediating Role of Psychological Well-being in the Impact of Autonomy on Loyalty and Innovative Work behavior of Fresh Graduates - Alkhawaldeh, Khleef A.; Issa, Reem; Hamdan, Saleh (Jordan Journal of Business Administration, 2024)
Qualified and promising fresh graduates are increasingly in demand, as they play an essential role in contributing to the future of institutions. This study aimed to investigate the impact of the autonomy of fresh graduates on their loyalty and innovative work behavior when mediated by the effect of their psychological well-being. The population of the study consisted of employed fresh graduates in Jordan. More specifically, the study population consisted of those who have graduated strictly two years ago or less. The variables of the study were measured by a questionnaire. Data was collected and analyzed and hypotheses were tested using correlation, linear regression and mediation analysis. The study found that the autonomy of fresh graduates has a significant positive impact on their psychological well-being. Additionally, the findings indicated that the psychological well-being of fresh graduates has a significant positive impact on their loyalty towards their employers, along with their innovative work behavior. Psychological well-being was found to have a mediating impact in the relationship between autonomy and loyalty and no mediating impact was found between autonomy and innovative work behavior. This study contributes to the literature by showing the mediating role of psychological well-being in the relationship between autonomy and loyalty.